Hire smart from the start : the entrepreneur's guide to finding, catching, and keeping the best talent for your company - Carvajal, Dave (Recorded Books, Inc., 2018)
Don't rely on instincts alone. Hiring. Is. King. The lesson seems so basic. Yet time after time, good companies stumble and lose their stride - just when they were poised for rapid growth. Why? Because their leaders treated hiring as a tedious chore. They posted an ad hoc ad. Took the first person with the right skills. Hired for immediate needs, rather than future flourishing. In Hire Smart from the Start, Dave Carvajal distills lessons gained from 20 years in the trenches, building out and staffing two enormously successful Internet startups and helping firms like Tumblr, Buddy Media, and Shutterstock land the talent they need to reach their greatest potential. Whether you're a high-tech entrepreneur taking a startup public, or a food truck vendor with a concept that's taking off, this book offers a proven formula to help you: - Find candidates whose values and working style fit your business - Spot the 5 types of applicants you should never, ever hire - Motivate "reach" candidates to leave their jobs and take a chance on your vision - Develop meaningful incentives that make people stay - And more Accelerate success: hire smart from the start. This book shows you how